Selection and optimization of scaffold materials to facilitate cellular response of C2C12 myoblasts. - Chia, Shermain Theng Xin. (2012)
The biological responses of cells have been shown to be dependent on both biochemical and biophysical factors. To date, a number of studies have explored the effects of mechanical factors such as substrate hydrophobicity, porosity and dissolution rate on cells. However, there is relatively less research on the role substrate elasticity plays in directing cellular behavior. This paper investigates the effect of substrate stiffness on adult muscle stem cells, or myoblasts. This was achieved by seeding C2C12 murine myoblasts cells on both fibrin (0.6 – 4.6 kPa) and Agarose gels (1.2 – 126.5 kPa) of different stiffness followed by observing subsequent proliferation, attachment and morphologies of the cells. C2C12 cells seeded on glass coverslips were used as control. The hypothesis tested was that as substrate stiffness increases, there is a corresponding increase in C2C12 proliferation, attachment, and morphological changes. Results obtained for the fibrin gels supported the hypothesis that there is a direct correlation between increased proliferation and attachment, change in cell morphology and substrate stiffness. However, findings from Agarose gel-based substrate were less consistent. The results suggest that C2C12 selectively responded to mechanical stiffness by altering cellular processes crucial in determining overall cellular activities towards physical cue in the cellular microenvironment.